Fenomena Budaya Bahasa “ Alay ” sebagai Bentuk Komunikasi Baru di Kalangan Remaja Zaman Sekarang - Ripahiyah Ripahiyah (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
The rapid development of technology and social media has significantly changed how teenagers communicate, including the emergence of the “alay” language phenomenon. Alay language is a form of non-standard communication widely used among teenagers, especially on social media platforms like Facebook. This study aims to identify the forms of alay language used by teenagers and analyze its impact on the proper use of the Indonesian language. A qualitative descriptive method was employed, with data collected through observations on social media. The results show that common forms of alay language include random capitalization, letter-to-number substitutions, excessive or reduced letter use, and the use of informal vocabulary. While this phenomenon reflects teenagers’ creative linguistic expression, it also poses negative implications for their proficiency in formal Indonesian. Overuse of alay language can lead to structural and semantic deterioration in language skills. Although it may be perceived as a part of youth identity and cultural expression, the use of alay language should be limited in formal communication settings. This study contributes to a deeper understanding of youth linguistic behavior and emphasizes the importance of preserving the quality of the national language.